THE MECHANISM OF THE FORMATION OF THE EXCHANGE RATE IN UZBEKISTAN AND ITS INFLUENCE ON THE LEVEL OF INFLATION - Matrzayev Zafarbek (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article explores the mechanism of exchange rate formation in Uzbekistan and its impact on inflation levels. By analyzing policy frameworks, economic dynamics, and empirical data, the study identifies key factors influencing currency valuation and inflationary trends. The article further examines global and local influences, providing actionable recommendations for policymakers to mitigate inflation risks while ensuring exchange rate stability.